ChemInform Abstract: Synthesis of Substituted Oxazoles from N‐Benzyl Propargyl Amines and Acid Chlorides. Issue 50 (10th December 2013) - v. Wachenfeldt, Henrik; Paulsen, Filip; Sundin, Anders; Strand, Daniel
Abstract Application of this method is demonstrated in total syntheses of romazarit (XII) and aleglitazar (XIII).